Use of #NutritionFacts to promote evidence-based nutrition information: X (formerly Twitter) hashtag analysis study - Matin, Maima; Joshi, Tanuj; Greger, Michael; Bin Matin, Farhan; Jóźwik, Artur; Wierzbicka, Agnieszka; Horbańczuk, Jarosław Olav; Willschke, Harald; Atanasov, Atanas G. (Frontiers in Public Health, 2023)
Nutrition is a key determinant of health, and the dissemination of reliable nutrition information to consumers is of great importance for public health. Especially with the rise of digital communication technologies and the wide-spread online misinformation, the provision of qualitative science-based information related to diet is of great importance. The NutritionFacts.org has been established as a prominent online source of evidence-based nutrition information. In this work we aimed to investigate the use of the associated hashtag #NutritionFacts on X (formerly Twitter) over a five years period, from 10 th of April 2018 to 10 th of April 2023. The conducted analysis with the use of Symplur Signals revealed that 18,998 tweets mentioning #NutritionFacts were posted by 6,136 X users, generating a total of 50,348,223 impressions (views). Both institutional and individual accounts were broadly participating in the dissemination of #NutritionFacts tweets, and the user location profiling indicated wide international engagement with the hashtag. This work indicates that #NutritionFacts has been established as an important hashtag utilized on X for the dissemination of evidence-based information related to nutrition.